ANALISIS PENGARUH MARKET TIMING ABILITY, STOCK SELECTION SKILL, EXPENSE RATIO DAN TINGKAT RISIKO TERHADAP KINERJA REKSA DANA SAHAM (Studi Pada Reksa Dana Saham Jenis KIK Periode 2009-2013) - Mungkas Putri, Cicilia Heny; Haryanto, A. Mulyo (Faculty of Economics and Business Diponegoro University, 2014)
Mutual funds are other investment opportunities with measurable risk and return is high enough with enough capital affordable to the community. Mutual funds have an Investment Manager with the ability and knowledge of the market it is or will happen. Therefore, mutual funds selected by investors because it is cheap, easy and